Price and Volume Effects of Voluntary Delisting in India - Manchanda, Shashank (Indian Journal of Finance, 2012)
This paper presents an empirical analysis of stock exchange delisting in India. Volume and wealth effects of such a delisting are investigated using data of 41 stocks voluntarily delisted from NSE, BSE and CSE. There is an increase in trading volume and decline in the firm's value after the announcement. The paper further shows that delisting from NSE\BSE leads to a decline in shareholders' wealth by 12.01% over the entire event window. Delisting from CSE does not elicit such a decline in value and the overall effect on firm value after CSE delisting is insignificant.